Penentuan Cemaran Mikroba Pada Jamu Pelangsing Yang Beredar Di Pasar Tarandam Padang - Rina Wahyuni; Vonda Perdana Lase; Harrizul Rivai (Jurnal Farmasi Higea, 2013)
Research about microbial countamination on slimming herbals powders, pills, capsules and caplets circulating in Tarandam market, Padang, has been evaluated. Powders had total plate count 0 x 106 CFU/g for PP (standard quality of powder was ≤ 1 x 106 CFU/g for total plate count). Pills had total plate count ≤ 0.5 x 105 CFU/g for MR (standard quality of pill was ≤ 1 x 105 CFU/g for total plate count). Capsules had total plate count 1.1 x 105 CFU/g for LM and 1.6 x 105 CFU/g for SA (standard quality of capsule was ≤ 1 x 104 CFU/g for total plate count) and Caples had total plate count 0.2 x 105 CFU/g for SC (standard quality of caplet was ≤ 1 x 104 CFU/g for total plate count). The total plate count calculation showed that only powders and pills were observed the BPOM standard quality of herbal drugs.The fungal count from all of samples were not observed the standard quality of herbal drugs. Powders had total fungal count 9 x 104 CFU/g for PP (standard quality of powder was ≤ 1 x 104 CFU/g for total fungal count). Pills had total fungal count 3.1 x 104 CFU/g for MR (standard quality of pill was ≤ 1 x 103 CFU/g for total fungal count). Capsules had total fungal count 2,3 x 104 CFU/g  for LM and 2.6 x 104 CFU/g for SA (standard quality of capsule was ≤ 1 x 103 CFU/g for total fungal count) and caplets had total fungal count 2.1 x 104 CFU/g  for SC (standard quality of caplet was ≤ 1 x 103 CFU/g for total fungal count).